Strengthening Gender-Responsive Climate-Smart Agriculture in Lesotho - Recha, John W.M.; Magagula, Futhi; Sinyangwe, Siwulanji; Kakuwa, Bridget; Zvaita, Justice; Gitau, Angela (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Lesotho’s agriculture sector remains highly vulnerable to climate variability, particularly droughts, erratic rainfall, and soil erosion. These risks disproportionately affect women and smallholder farmers, who face systemic barriers to land ownership, financial services, and agricultural decision-making. The workshop convened key stakeholders, including government ministries, research institutions, civil society organizations, women farmer leaders, and private sector actors,to co-create strategies that advance inclusive, equitable, and climate-resilient agricultural systems. Discussions highlighted that women’s empowerment, labour-saving technologies, access to climate information services, and integration of Indigenous knowledge are pivotal to scaling (climate-smart agriculture) CSA. Participants co-developed a national Action Matrix outlining short- and medium-term interventions in five thematic areas: land and water management, inputs and seed systems, labour-saving technologies, knowledge and communication, and financing and monitoring, evaluation, and learning (MEL). A Community of Practice (CoP) was also established to coordinate implementation, promote peer learning, and track progress on gender-responsive CSA in Lesotho. The workshop reaffirmed that achieving climate resilience requires systemic change anchored in inclusive policy design, participatory governance, and equitable access to resources. By combining scientific innovations with Indigenous wisdom and centering the voices of women and marginalized groups, Lesotho can chart a transformative pathway toward sustainable, gender-responsive climate-smart agriculture.